1985
DOI: 10.1007/bf00237103
|View full text |Cite
|
Sign up to set email alerts
|

Restriction endonuclease digest patterns of chromosomal DNA from nitrate-negative Campylobacter jejuni-like organisms

Abstract: High molecular weight chromosomal DNA was isolated from ten nitrate-negative campylobacters of human origin (gastric biopsies and faecal specimens). The DNA was digested with various restriction endonucleases and the patterns obtained were compared with those of Campylobacter coli, C. fetus subsp. fetus, C. jejuni and C. laridis reference strains. Electrophoresis of Hae III digests of DNA in 0.5% agarose gave excellent patterns which comprised at least 25 well-resolved bands with fragment sizes between about 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Both of these outbreak strain sets were different, however, by Lior serotyping, phage typing and DNA grouping. This finding highlights the excellent discriminatory power of the DNA grouping technique and confirms the value of using at least two different typing techniques when testing strains from different outbreaks [11][12][13][14][15]. Our results show clearly that both biotyping and DNA grouping have a major advantage over serotyping and phage typing in that strains of C. jejuni, which are untypable by the latter two methods, always give a result with biotyping and DNA grouping.…”
Section: Blotting and Hybridizationmentioning
confidence: 54%
See 2 more Smart Citations
“…Both of these outbreak strain sets were different, however, by Lior serotyping, phage typing and DNA grouping. This finding highlights the excellent discriminatory power of the DNA grouping technique and confirms the value of using at least two different typing techniques when testing strains from different outbreaks [11][12][13][14][15]. Our results show clearly that both biotyping and DNA grouping have a major advantage over serotyping and phage typing in that strains of C. jejuni, which are untypable by the latter two methods, always give a result with biotyping and DNA grouping.…”
Section: Blotting and Hybridizationmentioning
confidence: 54%
“…Comparisons of DNA digest patterns have been used in conjunction with serotyping in several epidemiological studies of C. jejuni [15,16] and in the characterization of cross-reacting serotypes of C. jejuni [27]. In the present study we have examined ribopatterns as well as total digest patterns because the former are comprised of less complex patterns of bands and facilitate between-strain comparisons.…”
Section: Blotting and Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent DNA dot blot hybridization studies have shown that the Australian strains are also closely related to the South African isolates (Steele, unpublished data). HaeIII restriction endonuclease digestion analysis of chromosomal DNA revealed distinct differences between strains from different geographical locations (10). The six West German gastric isolates all had almost identical band patterns, whereas the band patterns of the British (gastric) and Australian (fecal) isolates were different.…”
mentioning
confidence: 98%
“…All isolates were obtained from children that were less than 5 years old and were admitted to hospital with diarrhoea in Central Australia. Similar strains have now been isolated from a small number of aboriginal children in South and Western Australia, from children with diarrhoea in South Africa (9), and from gastric biopsies of adults in West Germany (7) and the United Kingdom (10).…”
mentioning
confidence: 99%